Comprehensive English learning model: Integrating digital storytelling for vocabulary and communication enhancement - Lia Agustina; Fitrotul Maulidiyah; Veri Hardinansyah Dja’far (Universitas Muhammadiyah Malang, 2026)
Storytelling has emerged as an effective instructional strategy that enhances students’ oral proficiency, vocabulary knowledge, comprehension, and overall literacy skills. By integrating imagination and emotional engagement, it promotes reading fluency, enriches vocabulary acquisition, and encourages the use of language in meaningful contexts. The study aims to investigate the influence of storytelling on students’ communicative competence and to evaluate its contribution to the improvement of their language abilities. The researchers used Classroom Action Research with 28 students from the Financial Accounting Program at the State Polytechnic of Malang, reveals that storytelling not only strengthens communicative competence but also increases learners’ motivation by linking personal experiences to classroom learning. Moreover, this approach fosters clarity in expression, improves both written and spoken communication, and cultivates digital literacy skills, all of which contribute to students’ academic advancement. Findings demonstrate that storytelling positively impacts oral communication by helping learners connect vocabulary with meaning and emotion. It also supports vocabulary expansion and deepens understanding of contextually appropriate language use. The quantitative results further confirm notable progress, as evidenced by an increase in the students’ pre-test scores—from 65 to 70 in the post-test—reflecting significant improvement in both oral communication proficiency and vocabulary development. The conclusion revealed that the model was implemented successfully, demonstrating its effectiveness in achieving the intended outcomes.